Порівняльна характеристика популярних «IAC» рішень для створення та менеджменту хмарної інфраструктури - Гусак, М. В. (ХНУРЕ, 2020)
In this publication, we will consider some of the most popular solutions for a cloud infrastructure manager using the IAC approach for the most popular cloud solutions. It's no secret that cloud computing occupies a large part of the digital services market. In this way, the issue of managing and optimizing the infrastructure and its cost is relevant. And the IAC approach has established itself as one of the best from this point of view and has several advantages. It is fast, simple, provides structure consistency, increases efficiency, allows you to optimize cost and minimize risks. We will try to examine in more detail the tools currently offered on the market for implementing the IAC approach.